Animal Models of Pathogenic New World Arenaviruses - Alexander V. Alvarado; Robert W. Cross; Thomas W. Geisbert; Courtney Woolsey (Microorganisms)
Since the emergence of Junín virus in 1953, pathogenic New World arenaviruses have remained a public health concern. These viruses, which also include Machupo virus, Guanarito virus, Sabiá virus, and Chapare virus, cause acute viral hemorrhagic fever and neurological complications, resulting in significant morbidity and mortality. Given the dearth of licensed therapeutics or vaccines against these pathogens, animal models of infection that recapitulate human manifestations of disease remain critically important to the development of efficacious medical countermeasures. Rodents and non-human primates have been successfully used to model human New World arenaviral infections, with guinea pigs, rhesus macaques, and cynomolgus macaques being the most successful models of infection for most major pathogenic New World arenaviruses. Here, we provide a highly comprehensive review of publicly reported animal models of pathogenic New World arenavirus infections, with a discussion of advantages and disadvantages for each model.